Synthesis of Dibenzosiloles through Electrocatalytic Sila‐Friedel‐Crafts Reaction. Issue 11 (8th April 2021) - Han, Pan; Yin, Mengyun; Li, Haiqiong; Yi, Jundan; Jing, Linhai; Wei, Bangguo
Abstract: A novel electrocatalyzed method for the preparation of dibenzosiloles was developed through intramolecular C−H/Si−H dehydrogenative coupling strategy starting from biarylhydrosilanes. Both electro‐donating and electro‐withdrawing substitution groups were tolerated for this transformation, and the desired dibenzosilole products could be obtained in moderate to excellent yields. A sila‐Friedel‐Crafts reaction mechanism was proposed on the basis of previous literature and our controlled experiments. Abstract :